각막반사를 이용한 수평사시 수술중 조정술 - 홍진표; Jin Pyo Hong; 유수리나; Soo Lie Nah Rhiu; 장윤희; Yoon Hee Chang; 장지호; Jee Ho Chang; 이종복; Jong Bok Lee (Daihan angwa haghoi jabji, 2008)
목적 : 한 눈의 시력이 없거나 아주 낮은 환자 중 협조가 가능한 수평사시 환자를 대상으로 각막반사를 이용하여 수술중 조정사시수술을 시행하고 조정의 양상에 대해 알아보았다. 대상과 방법 : 1997년 5월부터 2005년 4월까지 본원에서 각막반사를 이용하여 수술중 조정사시수술을 시행한 수평사시 환자의 의무기록을 후향적으로 조사하였다. 결과 : 전체 55명 중 외사시는 40명, 내사시는 15명 이었고 수술중 조정을 통해 수술량이 변경되었던 환자는 외사시 11명(27.5%), 내사시 4명(26.7%) 총 15명이었다. 성공한 환자는 외사시 35명(87.5%), 내사시 8명(53.3%), 수술량이 변경되었던 15명 중 성공적인 결과를 보인 환자는 11명(73.3%) 이었으며 이들은 술전 계획과 같은 수술량을 시행하였을 경우 부족 혹은 과교정 되었을 것이고 특히 두 근육 예정에서 한 근육만 수술한 4명(100%)은 수술중 조정술을 시행하지 않았다면 수술 후 심한 과교정이 되었을 것이다. 결론 : 주시하기가 어려울 정도로 시력이 없거나 아주 낮은 환자에서도 각막반사를 이용한 수술중 조정술을 통해 과교정 혹은 부족교정을 막을 수 있었고 비교적 높은 성공률을 기대할 수 있을 것이다. <한안지 49(1):143-147, 2008> Purpose: Using corneal reflex, we performed intraoperative adjustments in horizontal strabismus patients who had very poor visual acuities with good compliance and analyzed various aspects of intraoperative adjustment. Methods: We retrospectively reviewed the records of patients with horizontal strabismus who underwent intraoperative adjustment using corneal reflex from May 1997 to April 2005. We evaluated various aspects of intraoperative adjustment. Results: Fifty-five patients (40 exotropes, 15 esotropes) were included in our study. 11 of 40 extropes (27.5%) and 4 of 15 esotropes (26.7%) eventually underwent operations that were adjusted intraoperatively. Successful results were seen in 35 of 40 exotropes (87.5%) and 8 of 15 esotropes (53.3%). Fifteen patients (27.3%) received intraoperative adjustments, and of these patients 11 (20.0%) who had successful results would have experienced either undercorrection or overcorrection if their operation were performed as scheduled. Four patients underwent operation on one muscle rather than on the scheduled two muscles. All 4 of these patients (100%) would have experienced significantly large overcorrection had they not received intraoperative adjustment. Conclusions: Patients who would have had difficulty with fixation due to low visual acuity could avoid under- or overcorrection and are expected to have higher success rates because of intraoperative adjustment using corneal reflex. J Korean Ophthalmol Soc 49(1):143-147, 2008